Power optimization and economic evaluation of thermoelectric waste heat recovery system around a rotary cement kiln. (20th September 2019) - Mirhosseini, Mojtaba; Rezania, Alireza; Rosendahl, Lasse
Abstract: Cement rotary kiln is the main device utilized for industrial cement production in large scale. The shell temperature can reach several hundred Celsius degrees. Therefore, a thermoelectric waste heat recovery system can be utilized based on its advantages. In this study, an arc shaped absorber is designed and temperature distribution along the absorber circumference is obtained numerically. The calculated temperature is considered as the hot side temperature of thermoelectric generators (TEGs) that recover thermal energy on the absorber. In situations where the heat is free, the metric for designing a thermoelectric system is to reach the maximum power output. In order to reach regional optimal power from parametric design, the absorber length is divided into several sections. For efficient design of the TEG in each section, effect of significant parameters such as leg length and fill factor of the TEG and thermal resistance of the heat sink are studied. Effect of variation of the temperature and velocity magnitudes of the air next to the heat sinks is considered on thermal resistance and performance of the pin-fin heat sinks along the absorber. β-phase zinc antimonide (Zn4 Sb3 ) and magnesium tin silicide (Mg2 SiSn) are chosen as the p- and n-leg thermoelectric materials of the TEGs, respectively, because of their relatively high performance over the considered range of operating temperature. The results show that, staggered arrangement of the pin-fins is more effective for higher power generation and system performance compared to in-line arrangement of the fins. Moreover, by evaluation of the results, maximum matched power output in each section versus the fill factor and leg length can be determined in this study. The results show that, low fill factors between 0.05 and 0.2 can provide relatively a same maximum power as high fill factors. Furthermore, an economic evaluation is carried out to find optimal design of the TEG device for highest power generation and lowest investment cost. Various parameters of the cost function, such as cost of the bulk raw material (CB ), manufacturing cost associated with processing bulk material (CM, B ), areal manufacturing cost (CM, A ), heat exchanger cost (CH-EX ), balance of the system cost (CBoS ) and the installation cost (CI ) are taken into account in this study. The results show dominant parameter in the system cost is the heat sink. Highlights: The best place along the rotary cement kiln is found for waste heat recovery purpose. Design and optimization of arc shaped thermoelectric system around the kiln is done. Temperature distribution on absorber as hot side reservoir of TEG is obtained by CFD. A mathematical model by FEM is developed to design the arc shaped TEG system. Various design parameters of TEG and pin-fin heat sink are studied.